1977
DOI: 10.1111/j.1365-2133.1977.tb15067.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte transformation in subjects with nodulo-cystic acne

Abstract: Patients with severe nodulo-cystic acne are known to have elevated serum antibody levels and increased immediate hypersensitivity reactions to Propionibacterium acnes. This organism is the predominant bacterium in normal pilosebaceous follicles of human skin, and can be consistently isolated from pustular lesions in acne. Previously it had been observed that delayed cutaneous hypersensitivity reactions to P. acnes were negative in patients with acne. The present study investigated the proliferative response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 16 publications
4
15
0
1
Order By: Relevance
“…However, the lymphocyte responses obtained with the two P. acnes anti gens (1 and 2) correlated well with each other, and the skin tests with the antigens 2 and 3 also yielded parallel results. It seems therefore that the present results with these differ ent P. acnes antigens are comparable to the previous in vitro and in vivo findings [12,13,18], Some subjects with severe acne probably exhibit an im mune response different from that seen in ordinary acne. Patients with AF have shown decreased or lacking skin test reactivity to common bacterial antigens [14][15][16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the lymphocyte responses obtained with the two P. acnes anti gens (1 and 2) correlated well with each other, and the skin tests with the antigens 2 and 3 also yielded parallel results. It seems therefore that the present results with these differ ent P. acnes antigens are comparable to the previous in vitro and in vivo findings [12,13,18], Some subjects with severe acne probably exhibit an im mune response different from that seen in ordinary acne. Patients with AF have shown decreased or lacking skin test reactivity to common bacterial antigens [14][15][16].…”
Section: Discussionsupporting
confidence: 80%
“…Circulating antibodies against P. acnes have been demonstrated, and their levels seem to correlate with the severity of the acne [10, 11J. Fur ther evidence was presented by Puhvel et al [18], who showed that lymphocyte stimulation to P. acnes was signif icantly increased in 18 patients with nodulocystic acne when compared to acne-free subjects. In the present study, we investigated lymphocyte responses to P. acnes in the active and inactive phases of severe acne.…”
Section: Discussionmentioning
confidence: 86%
“…Outside the inner root sheath is the outer (external) root sheath. 24 In a small proportion, it produces considerable disfigurement. It is only one cell thick at the level of the bulb; it is thickest at the isthmus, where it starts to keratinize, forming a narrow zone of tricholemmal keratinization.…”
Section: The Normal Hair Folliclementioning
confidence: 99%
“…Ashbee et al [21]reported that patients with severe acne have significantly higher levels of complement fixing antibodies to P. acnes. Puhvel et al [22]showed that lymphocyte stimulation by P. acnes is significantly increased in patients with nodulocystic acne. Kersey et al [23]demonstrated that delayed skin test reactivity to P. acnes correlates with the severity of the disease.…”
Section: Abnormalities Of the Microbial Floramentioning
confidence: 99%